(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
According to the qualification description, the teacher of "Fine Art and Drawing" is a highly qualified specialist in folk decorative art, technical creativity, artistic design, leading technical and artistic design circles, as well as decorating schools and classrooms at the required level. is required. To date, it is necessary to creatively improve the content of the educational process in order to form the qualities listed above in the future teachers.